2019
DOI: 10.29228/turkishstudies.23496
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Öğretme-Öğrenme Anlayişlarinin Çeşi̇tli̇ Deği̇şkenler Açisindan İncelenmesi̇ (Kafkas Üni̇versi̇tesi̇ Örneği̇)

Abstract: The main purpose of this research is to investigate the teachinglearning conceptions of teacher candidates. Also, it is aimed to investigate whether constructivist and traditional teaching-learning conceptions of teacher candidates differed a significantly difference as statistically or not in terms of gender, type of program, class level, academic average and age range variables. The survey method was used to collect data in the research. The working group of the research consisted of 343 teacher candidates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Similarly, in the studies conducted by Can and Çelik (2018), Sosyal, Kutluca, and Radmard (2018), Tezci, Dilekli, Yıldırım, Kervan, and Mehmeti (2017), Çoşkun (2020), it was concluded that female teacher candidates were more prone to student-centered understanding compared to male teacher candidates. Akay ve Boz, (2011), Saracaloğlu et al (2013), Yaralı (2019), however, found that pedagogical beliefs did not differ concerning the gender variable of teachers and teacher candidates so that this researches also support the findings of this study. This study shows that gender is not an affecting factor for pedagogical belief systems and teacher efficacy because these dimensions should be affected by more cognitive and affective dimensions rather than a sociological dimension like gender.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, in the studies conducted by Can and Çelik (2018), Sosyal, Kutluca, and Radmard (2018), Tezci, Dilekli, Yıldırım, Kervan, and Mehmeti (2017), Çoşkun (2020), it was concluded that female teacher candidates were more prone to student-centered understanding compared to male teacher candidates. Akay ve Boz, (2011), Saracaloğlu et al (2013), Yaralı (2019), however, found that pedagogical beliefs did not differ concerning the gender variable of teachers and teacher candidates so that this researches also support the findings of this study. This study shows that gender is not an affecting factor for pedagogical belief systems and teacher efficacy because these dimensions should be affected by more cognitive and affective dimensions rather than a sociological dimension like gender.…”
Section: Discussionsupporting
confidence: 68%
“…Farklı branşlardaki öğretmenlerin ve öğretmen adaylarının çalışma grubunu oluşturduğu araştırmalara bakıldığında da benzer sonuçlar görülmüştür (Aslan, 2018;Çetinkaya ve Tabak, 2019;Süral ve Dedebali, 2018;Şahin, 2020). Bağcı, 2019;Ekinci, 2016;Ektem, 2018;Oğuz, 2011;Sevim, 2015;Yaralı, 2019;Yener ve Yılmaz, 2017) has been discovered that, overall, there is a statistically significant difference between the literacy levels of male and female primary school teachers. Overall, it was found that the average score for female teachers was greater than the average for male teachers.…”
Section: Tartişma Sonuç Ve öNeri̇lermentioning
confidence: 99%